Exploring math-identities of successful young women in post-compulsory mathematics - Emilie Gertz (Prometeica)
This paper aims to explore the math-identities among 33 young women in their meeting with post-compulsory upper secondary school mathematics. They have all chosen to advance mathematics to A-level, separating them from many other female students around the world. Through an identity framework consisting of four interrelated and overlapping dimensions (competence, performance, interest, and recognition) narrative interviews were conducted and analyzed to explore the interplay between the young women and the disciplinary educational context. Findings show an idealization of a narrow route to identify with mathematics for the selected ones who can produce correct answers. However, variation in the route to success relates to how they see themselves as either hard working or possessing special abilities for mathematics. The identification of these differences offers a broader understanding of successful young women’s identification with mathematics.